Tissue transfer techniques in reconstructive urology - Bryk, Darren J; Yamaguchi, Yuka; Zhao, Lee C. (Korean journal of urology, 2015)
Tissue transfer techniques are an essential part of the reconstructive urologist's armamentarium. Flaps and graft techniques are widely used in genital and urethral reconstruction. A graft is tissue that is moved from a donor site to a recipient site without its native blood supply. The main types of grafts used in urology are full thickness grafts, split thickness skin grafts and buccal mucosa grafts. Flaps are transferred from the donor site to the recipient site on a pedicle containing its native blood supply. Flaps can be classified based on blood supply, elevation methods or the method of transfer. The most used flaps in urology include penile, preputial, and scrotal skin. We review the various techniques used in reconstructive urology and the outcomes of these techniques.